Sodium Leak Channel in the Nucleus Accumbens Modulates Ethanol-Induced Acute Stimulant Responses and Locomotor Sensitization in Mice: A Brief Research Report - Wu, Yujie; Zhang, Donghang; Liu, Jin; Yang, Yaoxin; Ou, Mengchan; Liu, Bin; Zhou, Cheng (Frontiers in Neuroscience, 2021)
Ethanol can induce acute stimulant responses in animals and human beings. Moreover, repeated exposure to ethanol may produce increased sensitivity to its acute locomotor stimulant actions, a process referred to as locomotor sensitization. The molecular mechanism of the development of acute stimulant responses and locomotor sensitization by ethanol is not fully understood. Sodium leak channel (NALCN) is widely expressed in central nervous system and controls the basal excitability of neurons. The present study aims to determine whether NALCN is implicated in the ethanol-induced acute responses and locomotor sensitization in mice. Here, our results showed that ethanol caused acute stimulant responses in DBA/2J mice. Locomotor sensitization was successfully induced following the sensitization procedure. Accordingly, the expression levels of NALCN mRNA and protein in the nucleus accumbens (NAc) were markedly increased in the sensitization mice compared to the control mice. Knockdown the expression levels of NALCN in the NAc alleviated both the ethanol-induced acute responses and locomotor sensitization. Our findings indicate that upregulation of NALCN expression in the NAc contributes to the ethanol-induced acute stimulant responses and locomotor sensitization in DBA/2J mice.